Intrapelvic Wilms’ tumour: a rare entity for the most commonly encountered malignant renal tumour in children - Abd. Aziz, Azian; Govindarajan, Krishna Kumar; Chai , Yih Feng; Suboh, Roslina (Springer, 2010)
Purpose–Objective: Wilms’ tumour commonly presents as abdominal mass that originates from the renal parenchyma. We encountered and thus report and illustrate a case in which this malignant tumour filled and expand the renal pelvis with minimal parenchymal infiltration. Material and methods: A previously healthy 2-year-old boy was admitted to our hospital for painless gross hematuria. There was no abdominal swelling or distension. No history of trauma or bleeding disorder. On examination no abdominal or flank mass was palpable. The cause was revealed from radiological investigations: on Ultrasound, a solid well defined non-vascular lobulated mass was seen occupying and expanding the left renal pelvis with moderate hydronephrosis, on Computed Tomography (CT) as a well defined non-enhancing hypodense left intrapelvic renal mass and on Magnetic Resonance Imaging (MRI) as T1 hypointense and T2 hyperintense intrapelvic mass with evidence of upper pole parenchymal infiltration. Results: A left nephrectomy was performed and the histology revealed a Wilms’ tumour. Discussion and conclusion: Wilms’ tumour must be considered in children presenting with gross haematuria even when the location of the tumour is not typical; as illustrated in our case. The radiological images, gross specimen of the tumour and the histological images will be illustrated.